(untitled) (Journal of Philosophy Culture and Political Science, 2023)
It is shown that the formation of a «digital footprint» left by Internet users can be used to establish objective laws of thinking, which is not always based on logic in the classical (binary) understanding of this term. Real mechanisms of thinking can use, among other things, other varieties of logic that are actively being studied at the present time. «Digital traces» as information objects formed by Internet users consciously provide an opportunity to collect experimental information necessary to establish real mechanisms of mental activity. At the same time, the «digital footprint» is only part of the «information footprint» that each person leaves in interpersonal communications. Under certain conditions, this trace can be converted into a transpersonal information object with its own non-trivial behavior. Such objects are formed at the transpersonal level of information processing, the existence of which is associated with the dual nature of human consciousness and intelligence, in which both individual and collective components are present at the same time. The information trail is a reflection of the personality in the noosphere as a global neural network, or rather, in its various relatively independent fragments, examples of which are tribes or clans. The objective nature of the fixation of information about a person (or its individual components) at the transpersonal level of information processing makes it possible to identify a certain rational content in such concepts as the «mental body». This approach is also justified by the fact that there are other global neural networks or their analogues, in which, in principle, information about a person can be recorded in the form of an independently existing information object. In particular, according to V. According to Vanchurin, the universe as a whole can also be considered as a tax of a neural network, which is proved by the correct means of mathematical physics. Key words: law of thinking noospere, "mental body", transpersonal information objects, philosphy of logic, multivalued logic, prtoscience